2003
DOI: 10.1007/s00421-002-0736-8
|View full text |Cite
|
Sign up to set email alerts
|

Austrian Moderate Altitude Study 2000 (AMAS 2000). The effects of moderate altitude (1,700 m) on cardiovascular and metabolic variables in patients with metabolic syndrome

Abstract: We investigated the changes in the cardiovascular system [resting blood pressure (BP) and heart rate (HR), measured by means of a 24-h ambulatory BP and a holter-electrocardiogram (ECG)], glycemic parameters, and lipid metabolism of subjects suffering from metabolic syndrome during a 3-week sojourn at 1,700 m in the Austrian Alps. A total of 22 male subjects with metabolic syndrome were selected. Baseline investigations were performed at Innsbruck (500 m above sea level). During the 3-week altitude stay the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
86
3
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 24 publications
4
86
3
3
Order By: Relevance
“…Furthermore, 5-10 days of adaptation to hypoxia returns hyperglycemia to basal levels in healthy people (5). Moreover chronic hypoxic exposure reduces fasting insulin and improves insulin resistance in type 2 diabetic patients (44)(45)(46) and decreases the insulin dosage in type 1 diabetic patients (47,48). Of note, lower insulin levels or reduced insulin signaling is beneficial for health and longevity (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 5-10 days of adaptation to hypoxia returns hyperglycemia to basal levels in healthy people (5). Moreover chronic hypoxic exposure reduces fasting insulin and improves insulin resistance in type 2 diabetic patients (44)(45)(46) and decreases the insulin dosage in type 1 diabetic patients (47,48). Of note, lower insulin levels or reduced insulin signaling is beneficial for health and longevity (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…There were no differences in glycemia between subjects using insulin, metformin, sulfonylurea derivatives, dipeptidyl peptidase-4 inhibitors, or thiazolidinedione, although the number of subjects using these drugs was small (30). Schobersberger et al (31) found reductions in glucose concentrations and HOMA-IR after oral glucose loading, following 3 weeks of exercise at an altitude of 1,700 m in subjects with metabolic syndrome, four of whom had type 2 diabetes. These findings indicate increased insulin sensitivity at high to very high altitude and a possible additive effect of hypoxia and exercise in subjects with type 2 diabetes.…”
Section: Glucoregulatory Effects In Subjects With Diabetesmentioning
confidence: 99%
“…Augmented blood levels of immunological markers are a common finding during and after long-term strenuous exercise, where, due to skeletal muscle injury, infiammatory processes are induced. Although different changes of specific parameters like TNF-a, TNFRl, IL-Iß or IL-6 have been reportcd in the literature, high post-exercise values of one or more of the.se proinflammatory agonists have constantly been reported (4,12,20,21). Another limitation of the present study is that measurement of systemic parameters does not afways retlect significant changes in a local microenvironment.…”
Section: Discussionmentioning
confidence: 69%
“…Previous publications of data derived from the AMAS study reported favorable effects to a 3-week exposure to 1700 m on body mass, blood pressure, heart rate, Insulin resistance and glucose tolerance (11,12). Among the mediators chosen for the present study to represent an activated immune system in patients with metabolic Syndrome, only neopterin and sTNF-R75 showed a slight but transient increase on days 4 and/or 9 at moderate altitude as compared to baseline levels.…”
Section: Discussionmentioning
confidence: 79%